19th “Chinese Bridge” chinese proficiency competition - Ting, Hie Ling (UiTM Sarawak, 2021)
The "Chinese Bridge" is a Chinese Proficiency Competition for Foreign College Students and known for a large-scale international contest. This competition is important as a platform for international college students to learn the Chinese language and culture. Students who won the preliminary rounds held in their countries will be qualified to participate in the semi-finals and finals which will be held in China. As a reward, the winners will have the opportunity to receive a scholarship and further their studies in China.